Steady‐state MRA techniques with a blood pool contrast agent improve visualization of pulmonary venous anatomy and left atrial patency compared with time‐resolved MRA pre‐ and postcatheter ablation in atrial fibrillation. Issue 5 (2nd July 2015) - Rustogi, Rahul; Galizia, Mauricio; Thakrar, Darshit; Merritt, Bryce; Bi, Xiaoming; Collins, Jeremy; Carr, James C.
<x xml:space="preserve">Abstract</x> Purpose To compare steady‐state magnetic resonance angiography (SS‐MRA), using a blood pool contrast agent, with the established technique of time‐resolved MRA (TR‐MRA), in pulmonary vein mapping and left atrial patency. Materials and Methods Twenty‐one patients (12 males, age 58.3 ± 8.4 years; 9 females; 57 ± 10 years) undergoing pulmonary vein mapping were evaluated with TR‐MRA (TWIST) and SS‐MRA. Orthogonal measurements and areas for four veins per patient per technique were assessed by Friedman's test. Results Overall intertechnique mean difference for any pulmonary vein orthogonal measurement and area was 0.02 ± 0.34 cm (P = 0.705), and 0.2 ± 0.08 cm2 (P < 0.001). Interobserver correlation was strong for diameter and area measurements using the three methods with a range of 0.72–0.94, and 0.87–0.97, respectively. Left atrial appendage image quality score for TR‐MRA was significantly lower than the other two methods (P < 0.001). Both observers detected more stenosis on inversion recovery (IR)‐True FISP compared to TR‐MRA and IR‐FLASH. Conclusion SS‐MRA with a blood pool agent compared favorably to the established technique of TR‐MRA for quantitative assessment of pulmonary venous anatomy. SS‐MRA offers greater spatial resolution than TR‐MRA with increased confidence for ruling out left atrial appendage filling defect. J. Magn. Reson. Imaging 2015;42:1305–1313.